Emotional Intelligence in Students with Tendency to Involve in Cyberbullying - Ronella, Tiara; Sukmawati, Indah; Ifdil, Ifdil; Fikri, Miftahul (Current Issues in Counseling, 2025)
Various factors influence students' cyberbullying behavior, one of which is emotional intelligence. This study aims to describe the emotional intelligence of students who have a tendency to commit cyberbullying in terms of: (1) aspects of recognizing oneself, (2) aspects of managing emotions, (3) aspects of motivating oneself, (4) aspects of recognizing other people's emotions, (5) aspects of building relationships. The research method used is a quantitative method with a descriptive approach. The sample of this study was students XI and XII in who were identified as having a tendency to commit cyberbullying as many as 111 people. Sampling was determined by the total sampling technique. Data were obtained with a research instrument in the form of an emotional intelligence questionnaire with a Likert scale model. Data were analyzed using descriptive statistics. Based on the results of this study, data on the emotional intelligence of students who have a tendency to commit cyberbullying as a whole is in the high category, namely (59.16%%). It is hoped that related parties such as teachers and counselors can provide direction for students who commit cyberbullying with the hope that they still have emotional intelligence.